Public Health Outreach in Impoverished Areas of Cambodia: Addressing the Issues Related to Prescription Practices - Chisato Iba; Mira Namba; Yudai Kaneda; Takayuki Ando (University Library System, University of Pittsburgh, 2024)
During a two-week public health internship organized by Projects Abroad in impoverished areas in Cambodia, the authors participated in health check-ups and outreach activities. We identified issues such as polypharmacy and medication misuse. These problems stem from symptom-based prescriptions without considering individual patient conditions due to limited diagnostic equipments and medications. Our solution involved suggesting a documentation akin to Japan's prescription record books, and Drug Information Leaflets (DILs). Prescription record books would enable patients to record the medications they purchased at the pharmacy, so that physicians would know what medications patients are taking during their health checkups, and thus  prevent polypharmacy. In addition, the DILs included medication details and illustrations, considering the low literacy rates in the areas. We emphasized the need for sustained non-communicable diseases (NCDs) treatment and the potential of external perspectives to introduce innovative healthcare approaches and improvements within local communities.